Development, Validation, Identification and Estimation of Quinoline Yellow in the Levodopa and Carbidopa Pharmaceutical Combined dosage form by Ultra violet Visible Spectrophotometer (International Journal of Scientific Research in Science and Technology, 2024)
A simple, cost-effective, précised, accurate and robust Ultra Violet spectrophotometric method [1, 2 ] has been developed for the Identification and estimation of Quinoline Yellow in the Levodopa and Carbidopa tablet dosage forms. It is used as a colourant in the pharmaceutical tablet’s dosage form. UV scan of Quinoline yellow was taken from the entire UV range of 200 to 800 nm. From the spectrum, maximum absorption was observed at 414nm (λmax) for the Quinoline Yellow. Method was found to be specific with no interference due to blank and placebo, The method was linear with a correlation coefficient of more than 0.999, and Accuracy was in the range of 98.3 to 101.3, In the robustness study employed for standard and sample preparation showed no impact on the results, by deliberate changes proves method is robust and can be utilized for regular analysis. Method validation was performed with reference to ICH guidelines Q2R1.